2002
DOI: 10.1523/jneurosci.22-21-09244.2002
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Adenylate Cyclase-Activating Polypeptide and Sonic Hedgehog Interact to Control Cerebellar Granule Precursor Cell Proliferation

Abstract: Although positive and negative signals control neurogenesis in the embryo, factors regulating postnatal proliferation are less well characterized. In the vertebrate cerebellum, Sonic Hedgehog (Shh) is an efficacious mitogen for cerebellar granule neuron precursors (GNPs), and mutations activating the Shh pathway are linked to medulloblastoma, a tumor derived from GNPs. Although the mitogenic effects of Shh can be blocked by increasing cAMP or protein kinase A activity, the physiological factors antagonizing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
127
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(131 citation statements)
references
References 71 publications
(121 reference statements)
4
127
0
Order By: Relevance
“…PACAP and its receptors are actively expressed in the central nervous system during development, notably in the germinative neuroepithelia and migratory zones (9, 10), suggesting that PACAP could be involved in the regulation of neurogenesis and͞or cell differentiation (11). In agreement with this hypothesis, in vitro studies have shown that PACAP exerts growth cone attraction in cultured neural tube precursors from Xenopus laevis (12) and promotes survival and differentiation of rat cerebellar granule cells (13)(14)(15). In vivo, PACAP injection at the surface of the cerebellum of 8-day-old rats increases the number of granule neurons in the internal granule cell layer (16).…”
mentioning
confidence: 79%
“…PACAP and its receptors are actively expressed in the central nervous system during development, notably in the germinative neuroepithelia and migratory zones (9, 10), suggesting that PACAP could be involved in the regulation of neurogenesis and͞or cell differentiation (11). In agreement with this hypothesis, in vitro studies have shown that PACAP exerts growth cone attraction in cultured neural tube precursors from Xenopus laevis (12) and promotes survival and differentiation of rat cerebellar granule cells (13)(14)(15). In vivo, PACAP injection at the surface of the cerebellum of 8-day-old rats increases the number of granule neurons in the internal granule cell layer (16).…”
mentioning
confidence: 79%
“…Recent findings in animal models of excitotoxic injuries go in the same direction by linking Lot1 expression to neuroprotection and brain plasticity (10,60,61). Interestingly, in these models, a relationship between Lot1 expres- The role of cAMP in the maturation of newborn neurons is well accepted (13,14), and both PKA-dependent and PKA-independent pathways have been implicated in cAMP-mediated effects. Our study has shown that, in CGC, cAMP activation of Lot1 is PKA-and MEK/ ERK-dependent, as it was counteracted by specific pathway inhibitors.…”
Section: Discussionmentioning
confidence: 97%
“…Approximately 5 g of RNA were digested with 10 units of RNase-free DNase (Promega) for 30 min at 37°C. After DNase inactivation, RNA was retrotranscribed with an oligo(dT) [12][13][14][15][16][17][18] primer (0.5 M) and 200 units of Moloney murine leukemia virus reverse transcriptase (Invitrogen) according to the manufacturer's instructions. For real-time PCR, the following Lot1, glyceraldehyde-3-phosphate dehydrogenase, and c-fos primers were used: rat Lot, 5Ј-TTAGCTGCGTAGTTGCGTGTTA-3Ј (sense) and 5Ј-CGGGTCCCTGAAAAGAACACA-3Ј (antisense); glyceraldehyde-3-phosphate dehydrogenase, 5Ј-GAACATCATCCCTGCATCCA-3Ј (sense) and 5Ј-CCAGTGAGCTTCCCGTTCA-3Ј (antisense); and c-fos, 5Ј-TGGACCTGTCTGGTTCCTTC-3Ј (sense) and 5Ј-ATG-CACCAGCTCAGTCAGTG-3Ј (antisense).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations